Expression of MKK7 and Phospho-c-Jun in Glioma and Their Correlation - ZHI Cheng; LAI Miaoling; LIAO Degui; HAO Zhuofang; WANG Yezhong; WU Liqiang; LIU Sisi; ZENG Shulian; HUANG Ziyan; CHEN Danmin; YUAN Zhongmin (Zhongliu Fangzhi Yanjiu, 2019)
Objective To investigate the expression of phospho-c-Jun and MKK7 in gliomas and their correlation. Methods We collected and analyzed retrospectively 92 cases of gliomas, including 15 cases of diffuse astrocytoma, 5 cases of oligodendroglioma, 11 cases of anaplastic astrocytoma, 8 cases of anaplastic oligodendroglioma 53 cases of glioblastoma and 25 normal brain tissues adjacent to glioblastoma. The expression of c-Jun, phospho-c-Jun and MKK7 were detected by immunohistochemical staining. Glioma U87 cell line cultured in vitro was transfected with MKK4-siRNA, MKK7-siRNA and control siRNA for 48h, respectively. Western blot was performed to test the expression of c-Jun, phospho-c-Jun and MKK7. Results The expression of p-c-Jun and MKK7 in glioblastoma were significantly higher than those in other glioma and normal brain tissues adjacent to glioblastomas(P=0.000, P=0.000). The expression of MKK7 and phospho-c-Jun were positively correlated with WHO grading of gliomas (r＝0.494, P＝0.000; r=0.606, P=0.000). There was positive correlation between the expression of MKK7 and p-c-Jun (r=0.387, P=0.000). The knockdown of MKK7 suppressed c-Jun activities. Conclusion MKK7 promotes the development of glioblastoma by regulating the activity of c-Jun.